2018
DOI: 10.1111/jre.12600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of theaflavins on tissue inflammation and bone resorption on experimental periodontitis in rats

Abstract: Background and ObjectiveTheaflavins (TFs), the major polyphenol in black tea, have the ability to reduce inflammation and bone resorption. The aim of this study was to evaluate the effects of TFs on experimental periodontitis in rats.Material and MethodsThirty rats were divided into five groups: Control (glycerol application without ligation), Ligature (glycerol application with ligation), TF1 (1 mg/mL TF application with ligation), TF10 (10 mg/mL TF application with ligation), and TF100 (100 mg/mL TF applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Theaflavin. Theaflavin is a main polyphenol found in black tea made from the leaves of Camellia sinensis, and exerts anti-oxidant, anti-inflammatory and anti-tumor effects (15). In human gingival cells, theaflavin has been shown to decrease the secretion of interleukin (IL)-6 and IL-8 induced by LPS or tumor necrosis factor-α (TNF-α) (16,17).…”
Section: Evidence Of the Inhibitory Effect Of Various Naturally Occurmentioning
confidence: 99%
See 1 more Smart Citation
“…Theaflavin. Theaflavin is a main polyphenol found in black tea made from the leaves of Camellia sinensis, and exerts anti-oxidant, anti-inflammatory and anti-tumor effects (15). In human gingival cells, theaflavin has been shown to decrease the secretion of interleukin (IL)-6 and IL-8 induced by LPS or tumor necrosis factor-α (TNF-α) (16,17).…”
Section: Evidence Of the Inhibitory Effect Of Various Naturally Occurmentioning
confidence: 99%
“…In human gingival cells, theaflavin has been shown to decrease the secretion of interleukin (IL)-6 and IL-8 induced by LPS or tumor necrosis factor-α (TNF-α) (16,17). Recently, it was shown that theaflavin inhibited alveolar bone resorption in ligature-induced periodontitis rats, along with the reduction of immune cell infiltration and osteoclast formation in gingival tissues (15).…”
Section: Evidence Of the Inhibitory Effect Of Various Naturally Occurmentioning
confidence: 99%
“…It has been reported that several naturally occurring substances, such as curcumin and theaflavin alleviate the absorption of alveolar bones in animal periodontitis models (4,14). It has also been demonstrated that one of the sulfur-containing compounds present in garlic, diallylsulfide (DAS), reduces inflammatory reactions elicited by P.g.-derived lipopolysaccharide (LPS) in human gingival fibroblast cells (15).…”
Section: Sulfur-containing Amino Acids In Aged Garlic Extract Inhibitmentioning
confidence: 99%
“…It has been demonstrated that excessive inflammation in the gingival tissue, as well as an immune reaction triggered by the increased number of periodontal pathogens, such as Porphyromonas gingivalis (P.g. ), plays an important role in the severity and progression of periodontal diseases (3,4). Thus, the control of inflammation may help to delay disease progression or recover severe symptoms in periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…If periodontitis remains untreated, it can cause a significant degradation of periodontal tissues over time, which, in turn, causes apical migration of the junctional epithelium, and in the final stages, tooth loss [4][5][6]. If periodontal disease is not adequately treated, it can also lead to a significant reduction in chewing and aesthetic functions, which can be accompanied by impairment of social life and relationships in the most extensive cases [7][8][9].…”
mentioning
confidence: 99%